Anosognosia in dementia with Lewy bodies: a systematic review - Victor CALIL; Felipe Kenji SUDO; Gustavo SANTIAGO-BRAVO; Marco Antonio LIMA; Paulo MATTOS (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Anosognosia, i.e. lack of awareness of one’s own symptoms, is a very common finding in patients with dementia and is related to neuropsychiatric symptoms and worse prognosis. Although dementia with Lewy bodies (DLB) is the second most common form of degenerative dementia, literature on anosognosia in this disease is scarce. Objectives: This paper aimed to review the current evidence on anosognosia in patients with DLB, including its prevalence in comparison with other neurological conditions, its severity and anatomical correlations. Methods: Database searches were performed in PubMed, Web of Knowledge and PsycINFO for articles assessing anosognosia in DLB. A total of 243 studies were retrieved, but only six were included in the review. Results: Potential risk of selection, comparison or outcome biases were detected in relation to all the studies selected. Most of the studies used self-report memory questionnaires to assess cognitive complaints and compared their results to scores from informant-based instruments or to participants’ cognitive performance in neuropsychological tasks. Subjects with DLB had worse awareness regarding memory than healthy older controls, but the results concerning differences in anosognosia between DLB and Alzheimer’s disease (AD) patients were inconsistent across studies. Presence of AD pathology and neuroimaging biomarkers appeared to increase the prevalence of anosognosia in individuals with DLB. Conclusion: Anosognosia is a common manifestation of DLB, but it is not clear how its prevalence and severity compare with AD. Co-existence of AD pathology seems to play a role in memory deficit awareness in DLB.